Die deutsche Fischerei auf Blauleng 1987 im Nordost-Atlantik - Reinsch, H.H. (1988)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010